EMPOWERMENT OF THE MALAHING TOURISM VILLAGE COMMUNITY IN THE DEVELOPMENT OF THE CREATIVE ECONOMY - Ahmad Aznem; Muhamad; Endah Nurhawaeny (Jurnal Abdisci, 2024)
This community service aims to understand the empowerment of the tourism village community in the Development of Ecotourism Potential in Malahing Tourism Village, Tanjung Laut Indah Village, South Bontang District, Bontang City, East Kalimantan Province. The main problem is the sustainability of the creative economy community empowerment program for the community, especially batik craftsmen. The research method used in qualitative descriptive research displays data as it is in Malahing Tourism Village without a process of manipulation or other treatments, including exposure and clarification of existing data from a phenomenon that occurs. PT Pupuk Kalimantan Timur's CSR approach is carried out holistically, including social responsibility programs by paying attention to social, economic, and environmental aspects that emphasize the sustainability of community development for strategic stakeholders. The study results show that community empowerment in Malahing Tourism Village can independently improve the quality of life without dependence on the program organizer, CSR (Corporate Social Responsibility) PT Pupuk Kalimantan Timur.